Shift work domains and their interactions with empty calorie food/beverage consumption: A 14-day intensive longitudinal study. (May 2023) - Lin, Ting-Ti; Park, Chang G.; Kapella, Mary C.; Martyn-Nemeth, Pamela; Tussing-Humphreys, Lisa; Rospenda, Kathleen M.; Zenk, Shannon N.
Abstract: Background/objectives: Shift work has been linked to unhealthy eating behaviors such as imbalanced diet, or increased empty calorie food/beverage consumption. However, most research has focused on the impact of shift timing. The concept of shift work is complex, and it contains several domains such as shift timing, intensity, and speed. Previous studies have suggested that greater shift intensity and quicker shift speed may contribute to adverse health effects. However, evidence regarding associations between other domains of shift work and empty calorie food/beverage consumption has been relatively lacking. Therefore, the purpose of this study was to evaluate how other shift work domains related to empty calorie food/beverage consumption and whether different shift work domains interacted to influence the intake of foods or beverages. Design: A 14-day intensive longitudinal study employing ecological momentary assessment. Settings and participants: Eighty registered nurses working in 24 accredited Taiwanese hospitals (i.e., 9 medical centers, 12 regional hospitals, and 3 district hospitals) were recruited. Methods: During the study period, a convenience sample of 77 participants completed 2444 momentary surveys about empty calorie food/beverage consumption on a smartphone. Three shift work domains (shift timing, intensity, and speed) were evaluated based on registry-based work schedules. To study how these shift work domains influenced empty calorie food/beverage consumption, we employed three-level mixed-effects regression models for data analyses. Results: Findings suggested that greater night shift intensity increased the likelihood of sugar-sweetened beverage intake (odds ratio = 1.64, 95% confidence interval [1.01, 2.68]). The impacts of work shift intensity and shift timing on sugar-sweetened beverage consumption varied by shift speed. Among participants assigned a schedule with either medium or rapid shift speed, higher work shift intensity was associated with a higher probability of sugar-sweetened beverage consumption. Compared to day shifts, those who were assigned a quicker shift speed on evening shifts were more likely to consume sugar-sweetened beverages. However, associations between night shift intensity and sugar-sweetened beverage intake did not change by shift speed. Furthermore, shift intensity and shift timing did not interact to affect empty calorie food/beverage consumption. Conclusions: This study demonstrated assignments of shift schedules (i.e., high night shift intensity, more changes in shift timings) might influence workers' consumption of empty calorie foods/beverages. Therefore, identifying and mitigating hazardous shift schedules may help to improve shift workers' eating behaviors and benefit their overall health.